2021
DOI: 10.1021/acs.jmedchem.0c02008
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of GLPG1972/S201086, a Potent, Selective, and Orally Bioavailable ADAMTS-5 Inhibitor for the Treatment of Osteoarthritis

Abstract: There are currently no approved disease-modifying osteoarthritis (OA) drugs (DMOADs). The aggrecanase ADAMTS-5 is key in the degradation of human aggrecan (AGC), a component of cartilage. Therefore, ADAMTS-5 is a promising target for the identification of DMOADs. We describe the discovery of GLPG1972/S201086, a potent and selective ADAMTS-5 inhibitor obtained by optimization of a promising hydantoin series following an HTS. Biochemical activity against rat and human ADAMTS-5 was assessed via a fluorescence-bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 32 publications
(59 reference statements)
2
48
0
Order By: Relevance
“…It possesses an excellent selectivity profile in animal models and high stability in dog and human liver microsomes and hepatocytes. 35 Phase-1 clinical studies revealed favorable pharmacokinetics as well as a strong and consistent target engagement in both healthy subjects and OA patients (n=171). 36 In a phase-2 study (Roccella study) which investigated the efficacy and safety profile of three different once-daily oral doses of GLPG1972/S201086 (n=932), the change in 37 Another ADAMTS5targeting agent, M6495 an anti-ADAMTS5 Nanobody (Ablynx), showed an acceptable safety profile and dosedependent effects in a phase-1 study.…”
Section: Proteinases Inhibitors (Pi)mentioning
confidence: 99%
See 1 more Smart Citation
“…It possesses an excellent selectivity profile in animal models and high stability in dog and human liver microsomes and hepatocytes. 35 Phase-1 clinical studies revealed favorable pharmacokinetics as well as a strong and consistent target engagement in both healthy subjects and OA patients (n=171). 36 In a phase-2 study (Roccella study) which investigated the efficacy and safety profile of three different once-daily oral doses of GLPG1972/S201086 (n=932), the change in 37 Another ADAMTS5targeting agent, M6495 an anti-ADAMTS5 Nanobody (Ablynx), showed an acceptable safety profile and dosedependent effects in a phase-1 study.…”
Section: Proteinases Inhibitors (Pi)mentioning
confidence: 99%
“…It possesses an excellent selectivity profile in animal models and high stability in dog and human liver microsomes and hepatocytes. 35 Phase-1 clinical studies revealed favorable pharmacokinetics as well as a strong and consistent target engagement in both healthy subjects and OA patients (n=171). 36 In a phase-2 study (Roccella study) which investigated the efficacy and safety profile of three different once-daily oral doses of GLPG1972/S201086 (n=932), the change in cartilage thickness [in mm (SD)] of central medial tibiofemoral compartment of the target knee via quantitative MRI was −0.116 (0.27) for the placebo group and −0.068 (0.20), −0.097 (0.27) and 0.085 (0.22), for the low, medium and high dose, respectively.…”
Section: What Developments Have There Been In Clinical Oa Trials Currently In Active Phase 2 and 3 Trials?mentioning
confidence: 99%
“…The binding site of this ADAMTS5 mAb does not coincide with the aggrecan/versican substrate recognition site, which is located in the cysteine-rich and spacer domains ( Santamaria et al, 2019 ). Very recently, a Zn-coordinating small molecule active site inhibitor was described for ADAMTS5 (GLPG 1972) that displayed strong selectivity against ADAMTS1 and other MMPs with the exception of ADAMTS4, where the selectivity was only ∼8 fold ( Brebion et al, 2021 ). This selectivity is much lower compared to mAB-based exosite inhibitors against ADAMTS5, which did not bind to ADAMTS4 nor did they inhibit the protease or aggrecanase activity of ADAMTS4 ( Santamaria et al, 2015 ).…”
Section: Inhibitors Of Adamts Proteasesmentioning
confidence: 99%
“…Another small molecule inhibitor for ADAMTS5 (GLPG 1972, Galapagos) was tested in phase I/II trials (e.g. NCT03595618 , NCT04136327 ) ( Brebion et al, 2021 ). However, the phase II ROCCELLA trial ( NCT03595618 ) with cartilage thickness as the primary endpoint did not improve outcome in patients with osteoarthritis ( ThePharmaLetter, 2021 ).…”
Section: Inhibitors Of Adamts Proteasesmentioning
confidence: 99%
“…Compared with monoclonal antibodies, most small molecule inhibitors of ADAMTS5 are orally bioavailable ( Shiozaki et al, 2011 ), while the specificity of small molecule inhibitors is not that exquisite. Small molecule inhibitors were selected based on the structure of the ADAMTS5 protein, and the majority of inhibitors were developed based on the catalytic metalloproteinase domain ( Shiozaki et al, 2011 ; Chockalingam et al, 2011 ; Deng et al, 2012 ; Durham et al, 2017 ; Brebion et al, 2021 ; Nuti et al, 2013 ). The zinc-binding group in the catalytic metalloproteinase domain is the distinguishing structure of these inhibitors, such as hydroxamate and carboxylate ( Shiozaki et al, 2011 ; Deng et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%